Dominância fiscal e suas implicações sobre a política monetária no Brasil: uma análise do período 1999 - 2005 - Ázara, Alexandre de (2006)
The degree of freedom of monetary policy is an extremely relevant issue in a country with a floating exchange rate regime that adopts an inflation-targeting framework. If the country’s monetary authority does not have freedom to act, the inflation target can become inefficient. Specially, in a country where Fiscal Dominance prevails, monetary policy can have perverse effects on the Debt-to- GDP relationship, increasing the sovereign risk premium and the implicit probability of sovereign bond default. The purpose of this study is to perform the test of dominance from a model proposed by Olivier Blanchard in 2004, first testing whether the country was under dominance in 2002 and 2003 and then analyzing the result of this model through November 2005. Some modifications in the model’s variables, risk measures and interest rates are proposed. In addition, a coefficient stability test and the uncertainty caused during the lectoral period in 2002 have been included. Moreover, Central Bank actions during this period are analyzed to identify if its reaction was consistent with the dominance perspective presented in the original model. The conclusion is that Brazil, even after the suggested changes, remains in a situation of fiscal dominance according to the model description. However, the final result is about 20% of the observed level in 2004, with a significantly larger freedom to act for Brazilian monetary authorities in 2002 and 2003. In 2002, the Central Bank seems to have reacted to changes in inflation expectations and does not seem to have reached a fiscal dominance diagnosis. The elections were significant in explaining the increase in the default probability, but the change in variables didn’t significantly modify the result of the test. The proposed risk measure results in a better model to measure dominance in Brazil. The final message is that fiscal restrictions remain relevant in Brazil, but they are much less important than was considered by the original model.